The Legal Process for Addressing Illegal Fishing Using Trawls in Banda Aceh - Ramud, Susi Sartika (Abdurrauf Law and Sharia, 2025)
Article 9 paragraph (1) of Law Number 45 of 2009 amending Law Number 31 of 2004 on Fisheries prohibits the possession, control, carrying, and use of fishing gear that harms or disrupts the sustainability of fishery resources within Indonesia’s fisheries management areas. One of the violations identified in Banda Aceh is the use of trawl nets by local fishers during fishing operations. This study aims to analyze the process of resolving illegal fishing crimes involving trawl nets in Banda Aceh and to identify the challenges encountered during the legal process. This research employs an empirical juridical method, combining library research to examine relevant literature, legislation, and scholarly opinions, with field research through interviews with key informants. The findings reveal that the settlement process begins with the arrest of offenders by the Marine Police, followed by preliminary examination, the drafting of official investigation reports, and the transfer of the case to the prosecutor’s office before proceeding to trial at the Banda Aceh District Court. The main obstacles in law enforcement include limited facilities and infrastructure, low community awareness, and constraints faced by law enforcement officers. This study recommends strengthening monitoring facilities and enhancing legal education for fishers to prevent the continued use of trawl gear. [Pasal 9 ayat (1) Undang-Undang Nomor 45 Tahun 2009 tentang Perubahan atas Undang-Undang Nomor 31 Tahun 2004 tentang Perikanan menegaskan larangan kepemilikan, penguasaan, penggunaan, atau pembawaan alat penangkapan ikan yang dapat mengganggu atau merusak keberlanjutan sumber daya ikan. Salah satu pelanggaran terjadi di Kota Banda Aceh, yaitu penggunaan trawl oleh sebagian nelayan dalam aktivitas penangkapan ikan. Penelitian ini bertujuan untuk menjelaskan proses penyelesaian tindak pidana ilegal fishing menggunakan trawl di Kota Banda Aceh serta mengidentifikasi kendala yang dihadapi dalam penyelesaiannya. Metode penelitian yang digunakan adalah yuridis empiris melalui pendekatan kepustakaan untuk mengkaji literatur, peraturan perundang-undangan, dan pandangan sarjana, serta pendekatan lapangan melalui wawancara dengan informan terkait. Hasil penelitian menunjukkan bahwa proses penyelesaian tindak pidana ini dimulai dari penangkapan oleh Polisi Perairan, dilanjutkan dengan pemeriksaan awal, penyusunan Berita Acara Pemeriksaan (BAP), dan pelimpahan perkara ke kejaksaan hingga tahap persidangan di Pengadilan Negeri Banda Aceh. Hambatan utama dalam penyelesaian perkara meliputi keterbatasan sarana dan prasarana penegakan hukum, rendahnya kesadaran masyarakat, serta keterbatasan kapasitas aparat terkait. Penelitian ini merekomendasikan peningkatan fasilitas pengawasan dan edukasi hukum kepada nelayan untuk mencegah penggunaan trawl secara berulang.]